Islamic Boarding School Based Achievement Profiling in Pasuruan Regency - Ahmad Fatah Yasin; Muh. Hambali; Moh. Wardi (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to analyze the pattern of madrasas that imaged achievement based on pesantren. The method used is a case study qualitative method. The data collection technique is done through interviews, observation and documentation. The data analysis technique used consists of three stages of activities that occur simultaneously, namely; data reduction, data presentation, conclusion drawing/verification. The results showed that; Madrasa philosophy is able to personify the vision and mission that is side by side with the pesantren pattern which is the forerunner to the development of Madrasah Aliyah. The sustainable learning ecosystem of students after being in the madrasa is continued in the boarding school dormitory (pondokan). Its governance is supported by integrated management by aligning the madrasa curriculum with the pesantren curriculum based on the agreement of the two education managers. The implication of this research is that it can be used as input for the government, stakeholders, leaders, teachers, in making policies, so that the quality of education is more qualified and able to compete with other countries.